A novel one‐pot strategy of preparation of N‐phenylacrylamide‐styrene co‐polymer open tubular capillary column for peptides separation. Issue 24 (8th November 2020) - Sun, Genlin; Lu, Yao
Abstract: An open tubular capillary column (100 μm internal diameter and 120 cm length) was first fabricated with N ‐phenylacrylamide and styrene copolymer layer on the inner surface by in situ one‐pot strategy, while ethylene dimethacrylate was used as the cross‐linker. The pretreated silica‐fused capillary was reacted with 3‐trimethoxysilyl propyl methacrylate to attach a double‐bond ligand onto the inner surface of the capillary. Further, a thick and stabile copolymer layer was generated on the inner surface of the capillary by the novel method in situ one‐pot reaction of styrene‐ N ‐phenylacrylamide. The effects of reaction temperature and composition of the polymerization mixture on the morphology and permeability of the copolymer were investigated. The separation performance of the fabricated polymer columns were validated by separation of five synthetic peptides. The excellent efficiency (188 500 plates/m) of 100 μm internal diameter open tubular column with the separation media prepared by mixed one‐pot copolymerization has not been achieved via the isocratic elution mode. The column to column, intraday, and interday repeatabilities evaluated from the relative standard deviation were found better than 4%, exhibiting considerable repeatability of the column.